A New Method to Determine First-Order Transition Points from Finite-Size Data - Borgs, Christian; Janke, Wolfhard (Phys. Rev. Lett., 1991)
We consider a temperature driven first-order phase transition describing the coexistence of q ordered low-temperature phases and one disordered high-temperature phase at the in nite volume transition temperature T0. Analysing the exponential corrections to the usual heuristic formula of the periodic partition function in a box of volume V; Zper = P m exp(???? fmV ), where = 1=kBT and fm is the (metastable) free energy of the phase m, we propose several de finitions of a nite volume transition temperature T0(V ) which involve only exponential corrections with respect to T0. We test our propositions in the d = 2 Potts model for q = 5; 8 and 10 by means of Monte Carlo simulations, using the single cluster update procedure.